Relationships between physical fitness and match running demands during a futsal congested-weeks training camp - González-Fernández, Francisco; Ceylan, Halil; Silva, Rui Miguel; Clemente, Filipe; Bezerra, Pedro; Chen, Yung-Sheng (Biology of Sport, 2024)
This study examines the relationships between body composition, anthropometry and physical fitness measures, and internal and external load (match physical and running demands) during a congested period of an overseas futsal training camp. Eleven under-20 national futsal players participated in a eleven-day training camp. During the matches, exercise heart rate (HR) and locomotion profiles were recorded via a Polar Team Pro system as the players’ internal and external load. The friendly matches were scheduled on the training camp’s 2nd, 4th, 6th, 8th, and 10th days. A repeated-measures analysis of variance (ANOVA) and Pearson’s correlation coefficient were used for statistical analysis. The results revealed significant differences in sprint ( F = 2.74, p = 0.04, η 2 = 0.21), accelerations ( F = 3.63, p = 0.04, η 2 = 0.27), and decelerations ( F = 2.73, p = 0.04, η 2 = 0.21) performance between the five matches ( p < 0.05). Also, the overall body composition and physical fitness measures had large to very large correlations with match running demands during congested periods of futsal competition ( p < 0.05). In conclusion, the baseline body composition and the overall physical fitness measures may be essential factors in match running demands during a congested futsal match period. Futsal players who perform better in the 30–15 Intermittent Fitness Test can sustain a greater volume of highintensity accelerations during a congested period.